PELAKSANAAN PENDAFTARAN TANAH HAK MILIK MASYARAKAT DI GAMPONG LABUHAN KEUDE KECAMATAN SUNGAI RAYA KABUPATEN ACEH TIMUR - Cut Elidar; Rini Fitriani (Global Science Society, 2020)
Land registration is very important to be carried out by the community to obtain proof of ownership of the land that is the property. The first time to register a land must be measured, mapping, and bookkeeping land, as well as the granting of documents as proof of land rights. The process of measuring the soil must be ensured in advance to make boundary marks attached to each corner of the plot of land to be measured. After the measurement process, a mapping will be carried out, after which the land registration that has fulfilled the provisions will be issued a proof of rights, in the form of a certificate. Ownership of community land rights in Labuhan Keude Village so far does not have proof of certificate from the Office of the National Land Agency, they only have proof of ownership rights recorded in the village such as Letter C, Letter C which is a temporary certificate before the enactment of government regulations regarding land registration, can registration should be made directly to the Office of the National Land Agency. in order to immediately obtain a certificate of ownership of land rights. Population taken in community service is community leaders and gampong government, technically by providing socialization and discussion so that it is conveyed to the community to build community legal awareness of the importance of land registration. The purpose of this activity is to provide understanding to the community regarding the procedure for registering land in accordance with the rule of law and raising awareness of the importance of ownership of land title certificates